Polyunsaturated Fatty Acids Including Docosahexaenoic and Arachidonic Acid Bind to the Retinoid X Receptor α Ligand-binding Domain - Lengqvist, Johan; Mata de Urquiza, Alexander; Bergman, Ann-Charlotte; Willson, Timothy M.; Sjövall, Jan; Perlmann, Thomas; Griffiths, William J. (Molecular & cellular proteomics, 2004)
Nuclear receptors (NRs) constitute a large and highly conserved family of ligand-activated transcription factors that regulate diverse biological processes such as development, metabolism, and reproduction. As such, NRs have become important drug targets, and the identification of novel NR ligands is a subject of much interest. The retinoid X receptor (RXR) belongs to a subfamily of NRs that bind vitamin A metabolites (i.e. retinoids), including 9-cis-retinoic acid (9-cis-RA). However, although 9-cis-RA has been described as the natural ligand for RXR, its endogenous occurrence has been difficult to confirm. Recently, evidence was provided for the existence of a different natural RXR ligand in mouse brain, the highly enriched polyunsaturated fatty acid (PUFA) docosahexaenoic acid (DHA) (Mata de Urquiza et al. (2000) Science 290, 2140-2144). However, the results suggested that supra-physiological levels of DHA were required for efficient RXR activation. Using a refined method for ligand addition to transfected cells, the current study shows that DHA is a more potent RXR ligand than previously observed, inducing robust RXR activation already at low micromolar concentrations. Furthermore, it is shown that other naturally occurring PUFAs can activate RXR with similar efficiency as DHA. In additional experiments, the binding of fatty acid ligands to RXRalpha is directly demonstrated by electrospray mass spectrometry of the noncovalent complex between the RXR ligand-binding domain (LBD) and its ligands. Data is presented that shows the noncovalent interaction between the RXR LBD and a number of PUFAs including DHA and arachidonic acid, corroborating the results in transfected cells. Taken together, these results show that RXR binds PUFAs in solution and that these compounds induce receptor activation, suggesting that RXR could function as a fatty acid receptor in vivo.